PROTESTS AND MOBILIZATIONS IN THE GULF OF MEXICO (FIRST EDITION, MARCH 31, 2020, VERACRUZANA UNIVERSITY) - Hernández García, Daniela (2023)
This book includes works that are the products of researchers, professors, students, andactivists who, from academia, have spent years working and reflecting on emergingissues related to social movements in the Gulf of Mexico region, made up of the statesof Tamaulipas, Veracruz and Tabasco. In these spaces there are authoritarian politicalsystems in which illegality, violence, insecurity and uncertainty prevail.